Investing in Social Protection in Uganda: The case for the expansion of the Senior Citizens’ Grant - Uganda Social Protection Platform (UNICEF, 2017)
Senior citizens represent a vulnerable group in Uganda. For one they face economic constraints: approximately 85% of active older people engage in crop farming which is insufficient to provide a regular, stable income, and have no social security1. In addition, 85% of older persons in rural areas live in chronic poverty.2 Older citizens also face challenges due to disability as 66.8% of people above 60 have at least some difficulty in functional areas such as hearing, seeing, or others.3 Furthermore, their educational attainment is relatively low, with only 15.6% having completed either primary school or higher education levels.4 The impairments of older persons can affect future generations as older persons often have the task of caring for children.